The Cyclooctadepsipeptide Anthelmintic Emodepside Differentially Modulates Nematode, Insect and Human Calcium-Activated Potassium (SLO) Channel Alpha Subunits - Crisford, Anna; Ebbinghaus-Kintscher, Ulrich; Schoenhense, Eva; Harder, Achim; Raming, Klaus; O’Kelly, Ita; Ndukwe, Kelechi; O’Connor, Vincent; Walker, Robert J.; Holden-Dye, Lindy (PLoS neglected tropical diseases, 2015)
The anthelmintic emodepside paralyses adult filarial worms, via a mode of action distinct from previous anthelmintics and has recently garnered interest as a new treatment for onchocerciasis. Whole organism data suggest its anthelmintic action is underpinned by a selective activation of the nematode isoform of an evolutionary conserved Ca2+-activated K+ channel, SLO-1. To test this at the molecular level we compared the actions of emodepside at heterologously expressed SLO-1 alpha subunit orthologues from nematode (Caenorhabditis elegans), Drosophila melanogaster and human using whole cell voltage clamp. Intriguingly we found that emodepside modulated nematode (Ce slo-1), insect (Drosophila, Dm slo) and human (hum kcnma1)SLO channels but that there are discrete differences in the features of the modulation that are consistent with its anthelmintic efficacy. Nematode SLO-1 currents required 100 μM intracellular Ca2+ and were strongly facilitated by emodepside (100 nM; +73.0 ± 17.4%; n = 9; p < 0.001). Drosophila Slo currents on the other hand were activated by emodepside (10 μM) in the presence of 52 nM Ca2+ but were inhibited in the presence of 290 nM Ca2+ and exhibited a characteristic loss of rectification. Human Slo required 300 nM Ca2+ and emodepside transiently facilitated currents (100 nM; +33.5 ± 9%; n = 8; p<0.05) followed by a sustained inhibition (-52.6 ± 9.8%; n = 8; p < 0.001). This first cross phyla comparison of the actions of emodepside at nematode, insect and human channels provides new mechanistic insight into the compound's complex modulation of SLO channels. Consistent with whole organism behavioural studies on C. elegans, it indicates its anthelmintic action derives from a strong activation of SLO current, not observed in the human channel. These data provide an important benchmark for the wider deployment of emodepside as an anthelmintic treatment.